Line 1: Line 1:
 
Since all the <math>f_{n}</math> are AC, there exists <math>f_{n}^{'}</math> such that <math>f_{n}(x)=f_{n}(x)-f_{n}(0)=\int_{0}^{x}f_{n}^{'}(t)dt</math> and <math>f_{n}^{'}</math> are nonnegative almost everywhere.  
 
Since all the <math>f_{n}</math> are AC, there exists <math>f_{n}^{'}</math> such that <math>f_{n}(x)=f_{n}(x)-f_{n}(0)=\int_{0}^{x}f_{n}^{'}(t)dt</math> and <math>f_{n}^{'}</math> are nonnegative almost everywhere.  
  
Let <math>g_{n}(x)= \sigma_{1}^{n}f_{n}(x)</math>
+
Let <math>g_{n}(x)= \sum_{1}^{n}f_{n}(x)</math>

Revision as of 10:18, 10 July 2008

Since all the $ f_{n} $ are AC, there exists $ f_{n}^{'} $ such that $ f_{n}(x)=f_{n}(x)-f_{n}(0)=\int_{0}^{x}f_{n}^{'}(t)dt $ and $ f_{n}^{'} $ are nonnegative almost everywhere.

Let $ g_{n}(x)= \sum_{1}^{n}f_{n}(x) $

Alumni Liaison

Basic linear algebra uncovers and clarifies very important geometry and algebra.

Dr. Paul Garrett